A Novel SXT/R391 Integrative and Conjugative Element Carries Two Copies of the bla NDM-1 Gene in Proteus mirabilis - Jintao He; Long Sun; Linghong Zhang; Sebastian Leptihn; Yunsong Yu; Xiaoting Hua (mSphere, 2021)
The occurrence of carbapenemase-producing Proteus mirabilis